1994
DOI: 10.1213/00000539-199407000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin Does Not Increase Homologous Blood Requirements in Elective Coronary Bypass Surgery

Abstract: Studies have demonstrated increased homologous blood product requirements in patients on aspirin (ASA) undergoing cardiac surgery. We reexamined the influence of ASA therapy on hemorrhage and transfusion requirements in patients undergoing elective coronary artery bypass (CAB) surgery in light of recent transfusion-sparing practices and autologous cell salvaging techniques. Records from 197 patients who underwent reinfusion of postoperatively shed mediastinal autologous whole blood were retrospectively reviewe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(34 citation statements)
references
References 0 publications
2
31
0
1
Order By: Relevance
“…There were no significant differences between the study groups to haemorrhage in most procedures, with the exception of intracranial neurosurgery and possibly transurethral prostatectomy. As for transfusion rates, available data vary from "no significant differences between ASA-treated patients and controls" in cardiac surgery [53,54] to an "average increase of 30% in transfusion rate" in interdisciplinary review articles [24]. The complication rate of red blood cell transfusion has, however, been calculated to be only 0.4% [55].…”
Section: Discussionmentioning
confidence: 99%
“…There were no significant differences between the study groups to haemorrhage in most procedures, with the exception of intracranial neurosurgery and possibly transurethral prostatectomy. As for transfusion rates, available data vary from "no significant differences between ASA-treated patients and controls" in cardiac surgery [53,54] to an "average increase of 30% in transfusion rate" in interdisciplinary review articles [24]. The complication rate of red blood cell transfusion has, however, been calculated to be only 0.4% [55].…”
Section: Discussionmentioning
confidence: 99%
“…Although the Perioperative Blood Conservation Guidelines of the Society of Thoracic Surgeons/Society of Cardiovascular Anesthesiologists call for discontinuation of aspirin treatment in elective patients [2], several studies have failed to find increased perioperative blood loss or transfusion requirements in patients undergoing first-time or even repeated coronary artery surgery [22,23]. In a large retrospective study demonstrating the effect of aspirin on transfusion requirements, this effect was observed in only one quintile of patients (namely, those with the longest cardiopulmonary bypass times, greater number of women, repeated operations and more prevalent preoperative renal dysfunction) [24].…”
Section: Discussionmentioning
confidence: 99%
“…15,28 It should be noted, however, that several studies using strict transfusion criteria have demonstrated that preoperative aspirin does not increase allogeneic transfusion in elective primary or reoperative coronary artery surgery. 29,30 Standardized transfusion practice There is increasing evidence that postoperative blood transfusion should be guided by clinical indications and not only by specific hematocrit or hemoglobin values. 1,4,[31][32][33] In the present study, the use of clinical judgement as the main transfusion trigger resulted in a 50% decrease in allogeneic blood utilisation.…”
Section: The Blood Conservation Programmentioning
confidence: 99%